Teleology in biology, chemistry and physics education: what primary teachers should know - KOSTAS KAMPOURAKIS (Metaichmio Publications, 2007)
Recent research in cognitive psychology suggests that children develop intuitions that may clash with what is accepted by scientists, thus making certain scientific concepts difficult to understand. Children possess intuitions about design and purpose that make them provide teleological explanations to many different sorts of tasks. One possible explanation for the origin of the bias to view objects as made for something derives from an early sensitivity to intentional agents and to their behavior as intentional object users and object makers. What is important is that teleological explanations may not be exclusively restricted in biological phenomena, as commonly assumed. Consequently, primary school teachers should take that into account when teaching biology, chemistry or physics concepts and try to refrain from enforcing students' teleological intuitions.